Hospital-based Health Technology Assessment in Kazakhstan: 3 years' experience of one unit. (4th March 2019) - Avdeyev, Andrey; Tabarov, Adlet; Akhetov, Amir; Shanazarov, Nasrulla; Hailey, David; Kaptagayeva, Aygul; Zhanabekova, Liazzat; Gizatullina, Aliya; Makalkina, Larissa
Abstract : Objectives: The aim of this study was to describe the development and activities of the Hospital-Based Health Technology Assessment (HB-HTA) Unit in the Hospital of the President's Affairs Administration, one of the first examples of the implementation of HB-HTA into the practice of Kazakhstani hospitals. Methods: Details of the development of the Unit were obtained from the hospital's administrative records. The Unit's own records were used to describe the reports prepared and the clinical areas that were covered. Responses to recommendations in the Unit's reports were obtained from hospital administration and individual departments. Estimates of savings and payback periods were based on data from the hospital information system, and data submitted by manufacturers and distributors of medical equipment. Results: Fifty-one rapid- and mini-HTA reports were prepared by the Unit from 2015 to 2017. Seventeen health technologies (33 percent) were not recommended for implementation in hospital practice. Refusal to implement sixteen of these technologies saved approximately 1, 053, 500 USD. Of the thirty-four recommended health technologies, twenty-four were implemented to treat or diagnose 1, 376 patients, and eight others were included in plans for 2018–20. Of the twenty-four implemented health technologies, twelve did not require additional investments. The payback period of investments for the other twelve implemented technologies is not more than 3 years for six, less than 5 years for four, and more than 10 years for two technologies. Conclusions: Establishment of the HB-HTA Unit in the hospital created the basis for making informed managerial decisions; identifying key directions for strategic development; and improving hospital management.